Effect of yoruba language on primary school pupils’ academic achievement in numeracy in Ibadan, Oyo State (2017)
The study investigated the effect of Yoruba language (mother tongue) on pupils' academic achievement in Ibadan. The study adopted pretest- posttest control group quasi-experimental research design. Simple random sampling technique was used to select three local government areas and two primary schools in each of the local government areas using intact classes that were distinctly located from one another within the selected local government areas. The researcher randomly assigned four schools to the Yoruba Language Teaching Strategy (YLTS) and the remaining two schools to the conventional method (English Language) The participants comprised 197 primary' four pupils. One treatment package [Yoruba language instructional package (YLIP)] and one instrument [Numeracy Achievement Test (NAT)] were used in the study. The ability of the package and the instrument to measure the skill it has been designed for was established by the researchers. Thus the reliability co-efficient of 0.76 was obtained using K.R20. The data collected were analyzed using Analysis of covariance (ANCOVA). The result reveals that Yoruba language has significant effect on pupils, academic achievement in numeracy. Also, school locations do not significantly affect the academic achievement of primary school pupils and no significant interaction effect of Yoruba language and school location is revealed. The researchers advocated that Yoruba language as a medium of instruction should be used in teaching numeracy at the primary school level for the purpose of improving academic achievement. The federal government should take a second look at the policy of use of mother tongue for instruction to cover all level of primary school education, in order to prepare them for effective secondary' school education. The government should endeavour to monitor the teachers to know if the policies are being implemented. Keywords: Yoruba language, school location, academic achievement, primary school pupils.